Giant Asian honeybee stings induced acute myocarditis: a case report - NP Dinamithra; S Sivansuthan (Anuradhapura Clinical Society, 2013)
Hymenopterid stings and subsequent allergic reactions including fatal anaphylaxis are a common indication for emergency department visits worldwide. Less commonly, multiple wasp stings can result in multi-system involvement ranging from intravascular hemolysis, rhabdomyolysis, acute renal failure, cardiac involvement, hepatic dysfunction and occasionally thrombocytopenia and coagulopathy. Here we report one case of multiple Giant Asian honey bee stings induced myocarditis.